A method for obtaining negative electrode active material, negative electrode active material and application thereof

By screening the negative electrode active material of the core-shell structure, controlling the coverage rate and mass content of amorphous carbon, the problems of insufficient charging capacity at low temperatures and poor safety and circulation performance during long-term rapid charging are solved, and efficient balance performance is achieved.

CN116722116BActive Publication Date: 2025-03-18SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310706036.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2025-03-18
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The negative electrode active materials of existing lithium-ion batteries are insufficient in charging capacity at low temperatures and have poor safety and circulation performance during long-term rapid charging, making it difficult to take into account high and low temperature performance and safety.

Method used

By screening the negative electrode active material of the core-shell structure, with graphite as the core layer and amorphous carbon as the shell layer, the relationship between the coating rate, mass content and specific surface area of ​​the amorphous carbon is controlled to ensure that it is within the range of 0.005≤A*B/S≤0.075 to balance the kinetic performance, cyclic performance and high and low temperature performance.

Benefits of technology

It realizes the high charging capacity of lithium-ion batteries at low temperatures and good safety and cycle life during long-term fast charging, significantly improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116722116B_ABST
    Figure CN116722116B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and in particular, to a method for obtaining negative electrode active materials, negative electrode active materials and applications thereof. The method for obtaining negative electrode active materials of the present invention comprises the following steps: (a) providing a negative electrode active material to be screened, wherein the negative electrode active material to be screened is a core-shell structure, wherein the core layer is graphite and the shell layer is amorphous carbon; (b) obtaining the coverage rate A of amorphous carbon on the graphite surface, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S of the negative electrode active material to be screened in step (a), and screening out negative electrode active materials with a value of 0.005≤A*B / S≤0.075. The negative electrode active material obtained by the method of the present invention can improve the charging capacity of lithium-ion batteries, while ensuring that the lithium-ion batteries have good cycle life and safety when used for long-term fast charging, and the effect is remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a method for obtaining negative electrode active materials, negative electrode active materials and applications thereof. Background Art

[0002] Safety accidents of lithium-ion batteries often occur. Among them, the negative electrode active material is the key material of lithium-ion batteries, which plays a very important role in the cycle, fast charging, high and low temperature performance of lithium-ion batteries. The development of safe negative electrode materials is crucial to improving the safety performance of the entire battery. At present, with the increasing market requirements for the application of lithium-ion batteries, especially in order to meet the low temperature demand in northern winter, higher requirements are put forward for the low temperature performance of lithium-ion batteries. Therefore, lithium-ion batteries with excellent high safety, high and low temperature discharge performance and cycle performance have become the preferred products. Graphite materials have a layered structure, which leads to slow lithium ion insertion and extraction speed. The amorphous carbon coated on its surface, on the one hand, relies on the high diffusion rate of amorphous carbon in the charging and discharging process (the diffusion rate is about 10 times that of graphite) to increase the insertion and extraction rate of lithium ions; on the other hand, it can effectively reduce DCR and improve kinetic performance. However, excessive carbon coating leads to poor high temperature performance of the battery, which will bring risks to the safety performance of the battery. The large specific surface area of ​​graphite means smaller particles, more channels for lithium ion migration, shorter paths, and better rate performance. However, due to the large contact area with the electrolyte, the area of ​​the SEI film formed is also large, the irreversible capacity is large, and the initial efficiency will be reduced. In addition, more binder will be added, making processing difficult, and the slurry viscosity will be high, resulting in increased internal resistance and reduced cycle performance, leading to reduced safety performance.

[0003] In the existing technology, most of them are carbon coating on graphite, which can increase the rate of lithium ion deintercalation and effectively reduce DCR, improve low temperature performance and reduce its high temperature performance. Small particles and large specific surface area are conducive to improving its rate performance, but too large specific surface area means a large contact area with the electrolyte, more side reactions, and is not conducive to the battery cycle.

[0004] Therefore, it is crucial to overcome the above-mentioned defects and obtain a method for obtaining negative electrode active materials with balanced fast charging, high safety and low temperature performance to ensure that the negative electrode plates of lithium-ion batteries have high charging capacity at low temperatures, while ensuring that lithium-ion batteries have good safety during long-term fast charging use.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] An object of the present invention is to provide a method for obtaining a negative electrode active material, wherein the negative electrode active material obtained by the method can achieve a balance among cycle performance, low temperature performance and rate performance, and has excellent comprehensive performance.

[0007] Another object of the present invention is to provide a negative electrode active material that can ensure that the battery has a high charging capacity at low temperatures and at the same time ensure that the battery has good safety during long-term rapid charging use.

[0008] Another object of the present invention is to provide a negative electrode sheet.

[0009] Another object of the present invention is to provide a lithium ion battery.

[0010] Another object of the present invention is to provide an application of the lithium-ion battery in consumer electronics, power tools and electric vehicles.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] A method for obtaining a negative electrode active material comprises the following steps:

[0013] (a) providing a negative electrode active material to be screened, wherein the negative electrode active material to be screened is a core-shell structure, wherein the core layer is graphite and the shell layer is amorphous carbon;

[0014] (b) Obtaining the coverage rate A of amorphous carbon on the graphite surface, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S of the negative electrode active material to be screened in step (a), and screening out the negative electrode active material whose relationship among A, B and S satisfies 0.005≤A*B / S≤0.075.

[0015] In one implementation, the relationship between A, B and S satisfies: 0.013≤A*B / S≤0.06.

[0016] In one implementation, the relationship between A, B and S satisfies: 0.02≤A*B / S≤0.04.

[0017] In one embodiment, the range of A is 30% to 100%, the range of B is 0.5% to 6%, and the range of S is 0.8 to 2 m 2 / g.

[0018] In one embodiment, the method for obtaining the mass content B of the amorphous carbon in the negative electrode active material comprises:

[0019] (a1) drying a plurality of negative electrode active material standard samples with known amorphous carbon mass content, wherein the mass content of amorphous carbon in the negative electrode active material standard sample is B1;

[0020] (b1) performing thermogravimetric tests on the negative electrode active material standards respectively to obtain the thermal weight loss rates y1 of the amorphous carbon of the different negative electrode active material standards; the temperature range of the thermal weight loss rates is 200 to 620° C.;

[0021] The thermogravimetric test includes a first heat treatment and a second heat treatment, wherein the temperature of the first heat treatment is 25-400°C, the heating rate is 5-8°C / min, the temperature of the second heat treatment is 400-800°C, the heating rate is 2-4°C / min; the oxygen flow rate of the first heat treatment and the second heat treatment is 10-100 mL / min;

[0022] (c1) A linear fitting analysis was performed with the mass content of amorphous carbon in the negative electrode active material B1 as the horizontal coordinate and the thermal weight loss rate y1 as the vertical coordinate, and the relationship equation was obtained: y=1.9343x+0.1317;

[0023] (d1) Drying the negative electrode active material to be tested under the same conditions as step (a1), performing a thermogravimetric test under the same conditions as step (b1) to obtain its thermal weight loss rate y2, and obtaining the mass content B of amorphous carbon in the negative electrode active material to be tested according to the relationship curve equation in step (c1).

[0024] In one embodiment, the method for obtaining the specific surface area S of the negative electrode active material includes: testing with a specific surface area tester.

[0025] A negative electrode active material is obtained by the method for obtaining the negative electrode active material.

[0026] A negative electrode sheet comprises the negative electrode active material or the negative electrode active material obtained by the method for obtaining the negative electrode active material.

[0027] A lithium ion battery comprises the negative electrode sheet.

[0028] The lithium-ion battery is used in consumer electronics, power tools and electric vehicles.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The method for obtaining negative electrode active materials of the present invention obtains the coverage rate A of amorphous carbon on the graphite surface, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S of the negative electrode active material, and screens negative electrode active materials that satisfy 0.005≤A*B / S≤0.075. The obtained negative electrode active materials can balance the kinetic performance, cycle performance and high and low temperature performance of the negative electrode sheet.

[0031] (2) The battery obtained by using the negative electrode active material of the present invention has a high charging capacity and also has a good cycle life and safety when used for a long time with fast charging, and the effect is remarkable. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is the fitting line diagram of the negative electrode active material standard sample of the present invention. DETAILED DESCRIPTION

[0034] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0035] According to one aspect of the present invention, the present invention relates to a method for obtaining a negative electrode active material, comprising the following steps:

[0036] (a) providing a negative electrode active material to be screened, wherein the negative electrode active material to be screened is a core-shell structure, wherein the core layer is graphite and the shell layer is amorphous carbon;

[0037] (b) Obtaining the coverage rate A of amorphous carbon on the graphite surface, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S of the negative electrode active material to be screened in step (a), and screening out the negative electrode active material whose relationship among A, B and S satisfies 0.005≤A*B / S≤0.075.

[0038] The coverage rate in the present invention is defined as: the percentage of the coverage area of ​​amorphous carbon on the graphite (particle) surface to the total surface area of ​​the graphite (particle).

[0039] In one embodiment, the graphite includes artificial graphite.

[0040] In the negative electrode active material of the present invention, the coated amorphous carbon, on the one hand, relies on the high diffusion rate of amorphous carbon in the charge and discharge process (the diffusion rate is about 10 times that of graphite) to increase the insertion and extraction rate of lithium ions; on the other hand, it can effectively reduce DCR and improve kinetic performance; wherein the greater the coating rate A and the mass content B of amorphous carbon in the negative electrode active material, the more effectively the DCR is reduced, the kinetic performance is improved, and the low temperature performance is good; however, if the mass content B of amorphous carbon in the negative electrode active material is too large (i.e., too much coating), the high temperature performance of the battery will be reduced, and the safety will be reduced. A large specific surface area often means that its cycle storage performance is reduced. Therefore, the above-mentioned values ​​of A, B and S play an important role in the kinetic performance, cycle performance, power and high and low temperature performance of the battery; wherein, the value of A is large, the value of B is large (more residual carbon), the high temperature performance is poor, but the low temperature storage performance is good; and the cycle performance is related to the specific surface area. How to comprehensively control the cycle performance, high and low temperature storage performance and rate performance to achieve a balance is the focus and difficulty of the screening of negative electrode materials. The present invention can comprehensively realize the regulation of cycle performance, low temperature performance and rate performance by controlling A*B / S within a specific range. In particular, when the value of A*B / S is controlled within the range of 0.005 to 0.075, the cycle performance and high and low temperature performance can reach more than 88%, and the rate performance can also reach more than 89%, and the safety performance is relatively stable, thereby achieving a balance between cycle performance, high and low temperature storage performance and rate performance.

[0041] In summary, the present invention innovatively controls the coverage rate A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S to satisfy the relationship 0.005≤A*B / S≤0.075, and screens out the negative electrode active material. The negative electrode sheet prepared using the negative electrode active material can achieve a balance between fast charging, cycling and low temperature performance.

[0042] In one embodiment, A, B and S satisfy the relationship: 0.013≤A*B / S≤0.06.

[0043] In one implementation, A, B and S satisfy the relationship: 0.02≤A*B / S≤0.04.

[0044] In one embodiment, the range of A is 30% to 100%, for example, 30%, 40%, 45%, 50%, 55%, 60%, 70%, 80%, 90%, 95%, 100%; the range of B is 0.5% to 6%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, etc.; the range of S is 0.8 to 2m 2 / g, for example 0.8m 2 / g, 0.9m 2 / g, 1m2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g or 2m 2 / g, etc.

[0045] In one embodiment, the negative electrode active material of the present invention is obtained by purchase. The coverage rate A of amorphous carbon on the graphite surface is obtained through the supplier. In one embodiment, the negative electrode active material is derived from Guangdong Kaijin New Energy Technology Co., Ltd. In one embodiment, the negative electrode active material is derived from Hunan Zhongke Xingcheng Graphite Co., Ltd. In one embodiment, the negative electrode active material is derived from Hebei Kuntian New Energy Co., Ltd. In one embodiment, the negative electrode active material is derived from Zhejiang Carbon One New Energy Co., Ltd. In one embodiment, the negative electrode active material is derived from Shanghai Shanshan Technology Co., Ltd.

[0046] In one embodiment, the value of the coating amount B of the amorphous carbon is obtained by performing a TG test. In one embodiment, the method for obtaining the mass content B of the amorphous carbon in the negative electrode active material comprises:

[0047] (a1) drying a plurality of negative electrode active material standard samples with known amorphous carbon mass content at a drying temperature of 60 to 80° C. (e.g., 65° C., 70° C., etc.), wherein the mass content of amorphous carbon in the negative electrode active material standard sample is B1;

[0048] (b1) performing thermogravimetric tests on the negative electrode active material standards respectively to obtain the thermal weight loss rates y1 of the amorphous carbon of the different negative electrode active material standards; the temperature range of the thermal weight loss rates is 200 to 620° C.;

[0049] The thermogravimetric test includes a first heat treatment and a second heat treatment, wherein the temperature of the first heat treatment is 25-400°C, the heating rate is 5-8°C / min, the temperature of the second heat treatment is 400-800°C, the heating rate is 2-4°C / min; the oxygen flow rate of the first heat treatment and the second heat treatment is 10-100 mL / min;

[0050] (c1) A linear fitting analysis was performed with the mass content of amorphous carbon in the negative electrode active material B1 as the horizontal coordinate and the thermal weight loss rate y1 as the vertical coordinate, and the relationship equation was obtained: y=1.9343x+0.1317;

[0051] (d1) Drying the negative electrode active material to be tested under the same conditions as step (a1), performing a thermogravimetric test under the same conditions as step (b1) to obtain its thermal weight loss rate y2, and obtaining the mass content B of amorphous carbon in the negative electrode active material to be tested according to the relationship curve equation in step (c1).

[0052] In one embodiment, the negative electrode active material standard sample is derived from Hebei Kuntian New Energy Co., Ltd., and the mass content of amorphous carbon in the standard sample is provided by the supplier.

[0053] In one embodiment, the method for obtaining the specific surface area S of the negative electrode active material includes: testing with a specific surface area tester. In one embodiment, the specific surface area S of the negative electrode active material is tested by a conventional method in the prior art.

[0054] In one embodiment, the method for obtaining the specific surface area S of the negative electrode active material comprises the following steps:

[0055] (1) Open the protective gas valve, turn on the power of the equipment, and preheat for 30 minutes before starting the test;

[0056] (2) Carefully check whether the U-shaped sample tube and the glass funnel have cracks or notches, and whether the tube body and inner wall are clean. Only after confirming that they are intact can the mass of the empty sample tube be weighed and recorded as m1 (mg);

[0057] (3) Use a sample loading funnel to load the sample. The sample weight is 1000 ± 50 mg.

[0058] (4) Place the sample tube steadily in a beaker and weigh it. Record the mass of the sample before purging and the mass of the empty sample tube. This mass is only used as a reference for comparison with the total mass after purging.

[0059] (5) Purging: Before testing, control the inlet flow rate to 80 mL / min and the total outlet flow rate to 80 mL / min; it can clearly tell the operator whether the gas is turned on, and can check whether the sample tube is installed intact and whether the instrument is airtight; remove the physically adsorbed substances on the sample surface by degassing, and avoid irreversible changes on the surface; control the heating temperature to 200 °C and the heating time to 65 min;

[0060] (6) After the purge is completed, weigh the total mass of the sample tube m2 (mg), and the net weight of the sample m3 = m2-m1;

[0061] (7) Add liquid nitrogen: fill the sample cup with liquid nitrogen to 2 / 3 and the cold trap constant temperature cup to 1 / 3;

[0062] (8) Set the storage path, sample name, sample net weight and other parameters in the software interface to start the test; the instrument measures the sample adsorption amount using the direct comparison method, that is, a mixed gas of a certain ratio of carrier gas (He) and adsorbate gas (N2) flows through the sample to be tested, and the adsorption amount of the sample to be tested is obtained based on the concentration change before and after adsorption;

[0063] (9) After the experiment, record the experimental values ​​and confirm whether the main power of the instrument is turned off, whether the main valve of the cylinder is closed, and whether the cold trap constant temperature cup is taken out. After checking that everything is correct, tidy up the experimental table and clean the sample tube and funnel.

[0064] According to another aspect of the present invention, the present invention relates to a negative electrode active material obtained by using the above method for obtaining the negative electrode active material.

[0065] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the negative electrode active material as described above or the negative electrode active material obtained by the method for preparing the negative electrode active material as described above.

[0066] According to another aspect of the present invention, the present invention also relates to a lithium-ion battery, comprising the negative electrode sheet described above.

[0067] The battery of the present invention can achieve a balance between fast charging, cycling and low temperature performance.

[0068] According to another aspect of the present invention, the present invention also relates to the application of the lithium-ion battery in consumer electronics, power tools and electric vehicles.

[0069] The following is further explained in conjunction with specific embodiments and comparative examples.

[0070] Example 1

[0071] The method for obtaining negative electrode active material comprises the following steps:

[0072] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 50%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 2%, obtain the specific surface area S of the negative electrode active material, S is 1.8m 2 / g; A*B / S=0.0056, which is the negative electrode active material;

[0073] The method for obtaining the mass content B of amorphous carbon in the negative electrode active material includes:

[0074] (a1) drying a plurality of negative electrode active material standard samples with known amorphous carbon mass content, wherein the mass content of amorphous carbon in the negative electrode active material standard sample is B1;

[0075] (b1) performing multiple thermogravimetric tests on the negative electrode active material standard samples to obtain the thermal weight loss rate y1 of the amorphous carbon of different negative electrode active material standard samples; the temperature range of the thermal weight loss rate is 200 to 620° C.;

[0076] Each thermogravimetric test includes a first heat treatment and a second heat treatment, wherein the temperature of the first heat treatment is 25-400°C (increasing from 25°C to 400°C), the heating rate is 5°C / min, and the temperature of the second heat treatment is 400-800°C (increasing from 400°C to 800°C), the heating rate is 4°C / min; the oxygen flow rate of the first heat treatment and the second heat treatment is 20mL / min;

[0077] (c1) A linear fitting analysis was performed with the mass content of amorphous carbon in the negative electrode active material B1 as the horizontal axis and the thermal weight loss rate y1 as the vertical axis. The fitting line is as follows: Figure 1 As shown, the relationship equation is: y = 1.9343x + 0.1317;

[0078] In each standard sample, the specific values ​​of the mass content B1 of amorphous carbon in the negative electrode active material and the thermal weight loss rate y1 are shown in Table 1.

[0079] Table 1 B1 and thermal weight loss rate y1 of each standard sample

[0080]

[0081]

[0082] (d1) Drying the negative electrode active material to be tested under the same conditions as step (a1), and performing a thermogravimetric test under the same conditions as step (b1) to obtain its thermal weight loss rate y2. According to the relationship curve equation in step (c1), the mass content B of amorphous carbon in the negative electrode active material to be tested is obtained to be 2%.

[0083] The method for obtaining the specific surface area comprises the following steps:

[0084] (1) Open the protective gas valve, turn on the power of the equipment, and preheat for 30 minutes before starting the test;

[0085] (2) Carefully check whether the U-shaped sample tube and the glass funnel have cracks or notches, and whether the tube body and inner wall are clean. Only after confirming that they are intact can the mass of the empty sample tube be weighed and recorded as m1 (mg);

[0086] (3) Use a sample loading funnel to load the sample. The sample weight is 1000 ± 50 mg.

[0087] (4) Place the sample tube steadily in a beaker and weigh it. Record the mass of the sample before purging and the mass of the empty sample tube. This mass is only used as a reference for comparison with the total mass after purging.

[0088] (5) Purging: Before testing, control the inlet flow rate to 80 mL / min and the total outlet flow rate to 80 mL / min; check whether the sample tube is installed properly and whether the instrument is airtight; remove the physically adsorbed substances on the sample surface by degassing, and avoid irreversible changes on the surface; control the heating temperature to 200 °C and the heating time to 65 min;

[0089] (6) After the purge is completed, weigh the total mass of the sample tube m2 (mg), and the net weight of the sample m3 = m2-m1;

[0090] (7) Add liquid nitrogen: fill the sample cup with liquid nitrogen to 2 / 3 and the cold trap constant temperature cup to 1 / 3;

[0091] (8) Set the storage path, sample name, sample net weight and other parameters in the software interface to start the test; the instrument measures the sample adsorption amount using the direct comparison method, that is, a mixed gas of a certain ratio of carrier gas (He) and adsorbate gas (N2) flows through the sample to be tested, and the adsorption amount of the sample to be tested is obtained based on the concentration change before and after adsorption;

[0092] (9) After the experiment, record the experimental values ​​and confirm whether the main power of the instrument is turned off, whether the main valve of the cylinder is closed, and whether the cold trap constant temperature cup is taken out. After checking that everything is correct, tidy up the experimental table and clean the sample tube and funnel.

[0093] Example 2

[0094] The method for obtaining negative electrode active material comprises the following steps:

[0095] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 50%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 3%, obtain the specific surface area S of the negative electrode active material, S is 1.5m 2 / g; A*B / S=0.0100;

[0096] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0097] Example 3

[0098] The method for obtaining negative electrode active material comprises the following steps:

[0099] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 50%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 4%, obtain the specific surface area S of the negative electrode active material, S is 1.5m 2 / g; A*B / S=0.0133;

[0100] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0101] Example 4

[0102] The method for obtaining negative electrode active material comprises the following steps:

[0103] The coverage rate A of the amorphous carbon on the graphite surface in the composite material is obtained, A is 70%, the mass content B of the amorphous carbon in the negative electrode active material is obtained, B is 2%, and the specific surface area S of the negative electrode active material is obtained, S is 1.4 m 2 / g; A*B / S=0.0093;

[0104] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0105] Example 5

[0106] The method for obtaining negative electrode active material comprises the following steps:

[0107] The coverage rate A of the amorphous carbon on the graphite surface in the composite material is obtained, A is 70%, the mass content B of the amorphous carbon in the negative electrode active material is obtained, B is 3%, and the specific surface area S of the negative electrode active material is obtained, S is 1.35m 2 / g; A*B / S=0.0150;

[0108] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0109] Example 6

[0110] The method for obtaining negative electrode active material comprises the following steps:

[0111] The coverage rate A of the amorphous carbon on the graphite surface in the composite material is obtained, A is 70%, the mass content B of the amorphous carbon in the negative electrode active material is obtained, B is 4%, and the specific surface area S of the negative electrode active material is obtained, S is 1.3m 2 / g; A*B / S=0.0207;

[0112] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0113] Example 7

[0114] The method for obtaining negative electrode active material comprises the following steps:

[0115] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 1%, and obtain the specific surface area S of the negative electrode active material, S is 1.6 m 2 / g; A*B / S=0.0063;

[0116] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0117] Example 8

[0118] The method for obtaining negative electrode active material comprises the following steps:

[0119] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 2%, and obtain the specific surface area S of the negative electrode active material, S is 1.6 m 2 / g; A*B / S=0.0125;

[0120] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0121] Example 9

[0122] The method for obtaining negative electrode active material comprises the following steps:

[0123] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 3%, obtain the specific surface area S of the negative electrode active material, S is 1.3m 2 / g; A*B / S=0.0231;

[0124] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0125] Example 10

[0126] The method for obtaining negative electrode active material comprises the following steps:

[0127] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 4%, obtain the specific surface area S of the negative electrode active material, S is 1.2m 2 / g; A*B / S=0.0333;

[0128] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0129] Embodiment 11

[0130] The method for obtaining negative electrode active material comprises the following steps:

[0131] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 5%, obtain the specific surface area S of the negative electrode active material, S is 1.0 m 2 / g; A*B / S=0.0500;

[0132] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0133] Example 12

[0134] The method for obtaining negative electrode active material comprises the following steps:

[0135] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 6%, obtain the specific surface area S of the negative electrode active material, S is 0.8m 2 / g; A*B / S=0.0750;

[0136] The method for obtaining the coverage A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this embodiment is the same as that in Example 1.

[0137] Comparative Example 1

[0138] The method for obtaining negative electrode active material comprises the following steps:

[0139] The coverage rate A of amorphous carbon on the graphite surface is 0, the mass content B of amorphous carbon in the negative electrode active material is 0, and the specific surface area S of the negative electrode active material is 1.8 m 2 / g; A*B / S=0;

[0140] The method for obtaining the coverage ratio A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this comparative example is the same as that in Example 1.

[0141] Comparative Example 2

[0142] The method for obtaining negative electrode active material comprises the following steps:

[0143] The coverage rate A of the amorphous carbon on the graphite surface in the composite material is obtained, A is 30%, the mass content B of the amorphous carbon in the negative electrode active material is obtained, B is 1%, and the specific surface area S of the negative electrode active material is obtained, S is 1.7 m 2 / g; A*B / S=0.0017;

[0144] The method for obtaining the coverage ratio A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this comparative example is the same as that in Example 1.

[0145] Comparative Example 3

[0146] The method for obtaining negative electrode active material comprises the following steps:

[0147] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 8%, obtain the specific surface area S of the negative electrode active material, S is 1.0 m 2 / g; A*B / S=0.08;

[0148] The method for obtaining the coverage ratio A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this comparative example is the same as that in Example 1.

[0149] Comparative Example 4

[0150] The method for obtaining negative electrode active material comprises the following steps:

[0151] Obtain the coverage rate A of the amorphous carbon on the graphite surface in the composite material, A is 100%, obtain the mass content B of the amorphous carbon in the negative electrode active material, B is 10%, obtain the specific surface area S of the negative electrode active material, S is 0.8m 2 / g; A*B / S=0.1000;

[0152] The method for obtaining the coverage ratio A, the mass content B of amorphous carbon in the negative electrode active material and the specific surface area S in this comparative example is the same as that in Example 1.

[0153] Experimental example

[0154] 1. The negative electrode active materials in the embodiment and the comparative example are respectively prepared into soft-pack batteries, and the specific method includes:

[0155] The negative electrode active material, conductive agent SP, CMC and SBR were uniformly mixed to obtain a negative electrode slurry, wherein the mass ratio of the negative electrode active material, conductive agent SP, CMC and SBR was 95:1.5:1.5:2.0, the negative electrode slurry was coated on a 6μm copper foil of the negative electrode by a coater, and a negative electrode sheet was prepared by a roller press; lithium iron phosphate was used as the positive electrode, a lithium salt LiPF6 solution (concentration 1 mol / L), EC (ethylene carbonate) and DEC (diethyl carbonate) with a volume ratio of 1:1 as the solvent were used as the electrolyte, and celgard 2400 was used as the separator to prepare a 5Ah soft-pack battery.

[0156] The soft-pack batteries prepared in the examples and comparative examples were tested for cycle performance, rate performance and high-temperature storage performance, and the specific test parameters were set as follows:

[0157] 1. Cycle performance: 1C / 1C, 2.5-3.65V, 25±3℃.

[0158] 2. Rate performance: 2C constant current ratio, constant current capacity / (constant current capacity + constant voltage capacity).

[0159] 3. Low temperature storage performance: The lithium-ion battery is charged to 3.65V at a rate of 0.1C, and its capacity is tested as A0. It is then placed at a temperature of -20±3℃ for 7 days, and then its capacity A1 is tested at room temperature. It is then charged to 3.65V and its capacity A2 is tested. The capacity recovery is then calculated as A2 / A0*100%, i.e., the low temperature storage performance.

[0160] 4. High temperature storage performance: The lithium-ion battery is charged to 3.65V at a rate of 0.1C, and its capacity is tested as A0. It is then placed at a temperature of 60±3℃ for 7 days, and then its capacity A1 is tested at room temperature. It is then charged to 3.65V and its capacity A2 is tested. The capacity recovery is then calculated as A2 / A0*100%, i.e., high temperature storage performance.

[0161] The negative electrode active materials in the embodiment and the comparative example are respectively prepared into button cells, and the specific method includes:

[0162] The negative electrode active material, conductive agent SP, CMC and SBR are uniformly mixed to obtain a negative electrode slurry, wherein the mass ratio of the negative electrode active material, conductive agent SP, CMC and SBR is 95:1.5:1.5:2.0; the negative electrode slurry is coated on the negative electrode collector by a coater, and the negative electrode sheet is prepared by a roller press; a lithium salt LiPF6 solution (concentration 1 mol / L) and a solvent with a volume ratio of 1:1 EC (ethylene carbonate) + DEC (diethyl carbonate) are used as the electrolyte, a lithium sheet is used as the positive electrode, and celgard 2400 is used as the separator to assemble a button half-cell.

[0163] After the button cells obtained in the embodiment and the comparative example were cycled twice, fully charged samples were retained for DSC testing, and specific detection parameter settings are shown in Table 2 below:

[0164] Table 2 Detection parameter settings

[0165]

[0166] DSC test: After fully charged and disassembled, the electrode is cleaned with DMC and dried before DSC test. The temperature range is 20-450℃ and the heating rate is 5℃ / min.

[0167] The performance test results of the above soft pack batteries and button batteries are shown in Table 3.

[0168] Table 3 Battery performance test results

[0169]

[0170]

[0171] As shown in Table 3, when the value of A*B / S is controlled within the range of 0.005 to 0.0075, the rate performance of Examples 1 to 12 of the present invention can be controlled to be above 85%, and the cycle performance can be made to be above 90%, and the high and low temperature performance can be made to be above 88%, which can effectively achieve the balance between the fast charge, cycle and high and low temperature performance of the negative electrode sheets prepared by the negative electrode active material group. However, in Comparative Examples 1 and 2, the low coverage, small mass content of amorphous carbon, poor kinetic performance, low temperature difference, and large specific surface area lead to deviations in the cycle performance; in Comparative Examples 3 and 4, due to the large coverage, large mass content of amorphous carbon, good kinetics, good low temperature performance, but small specific surface area, poor rate performance, and poor safety performance.

[0172] By comparing Examples 3 to 6, Examples 8 to 11 with Examples 1, 2, and 12, it can be seen that when the value of A*B / S is controlled within the range of 0.013 to 0.05, the balance of high and low temperature performance can be taken into account, and the rate performance, cycle performance, and safety performance can be comprehensively improved.

[0173] By comparing Examples 9 to 10 with Examples 1-8 and Examples 11-12, it can be seen that when the value of A*B / S is controlled within the range of 0.02 to 0.04, not only can the rate performance, cycle performance, and low temperature performance reach more than 92%, but the high temperature performance can also reach more than 93%, and the decomposition temperature and energy of the fully charged DSC test of the electrode are relatively moderate, while taking into account the safety of the battery. That is, under the condition of having relatively excellent fast charging performance, the negative electrode active material that can simultaneously improve the cycle and high and low temperature performance of the negative electrode is effectively screened out.

[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for obtaining a negative electrode active material, characterized in that: The following steps are involved: (a) providing a negative electrode active material to be screened, wherein the negative electrode active material to be screened is a core-shell structure, wherein the core layer is graphite and the shell layer is amorphous carbon; (b) obtaining the coverage rate A of amorphous carbon on the graphite surface, the mass content B of amorphous carbon in the negative electrode active material, and the specific surface area S of the negative electrode active material of the negative electrode active material to be screened in step (a), and screening out the negative electrode active material whose relationship between A, B and S satisfies 0.005≤A*B / S≤0.075; The range of A is 30% to 100%, the range of B is 0.5% to 6%, and the range of S is 0.8 to 2 m 2 / g; The method for obtaining the mass content B of the amorphous carbon in the negative electrode active material comprises: (a1) drying a plurality of negative electrode active material standard samples with known amorphous carbon mass content, wherein the mass content of amorphous carbon in the negative electrode active material standard sample is B1; (b1) performing thermogravimetric tests on the negative electrode active material standards respectively to obtain the thermal weight loss rates y1 of the amorphous carbon of the different negative electrode active material standards; the temperature range of the thermal weight loss rates is 200 to 620° C.; The thermogravimetric test includes a first heat treatment and a second heat treatment, wherein the temperature of the first heat treatment is 25-400°C, the heating rate is 5-8°C / min, the temperature of the second heat treatment is 400-800°C, the heating rate is 2-4°C / min; the oxygen flow rate of the first heat treatment and the second heat treatment is 10-100 mL / min; (c1) A linear fitting analysis was performed with the mass content of amorphous carbon in the negative electrode active material B1 as the horizontal coordinate and the thermal weight loss rate y1 as the vertical coordinate, and the relationship equation was obtained: y=1.9343x+0.1317; (d1) Drying the negative electrode active material to be tested under the same conditions as step (a1), performing a thermogravimetric test under the same conditions as step (b1) to obtain its thermal weight loss rate y2, and obtaining the mass content B of amorphous carbon in the negative electrode active material to be tested according to the relationship curve equation in step (c1).

2. The method for obtaining negative electrode active material according to claim 1, characterized in that: The relationship between A, B and S satisfies: 0.013≤A*B / S≤0.

06.

3. The method for obtaining negative electrode active material according to claim 2, characterized in that: The relationship between A, B and S satisfies: 0.02≤A*B / S≤0.

04.

4. The method for obtaining negative electrode active material according to claim 1, characterized in that: The method for obtaining the specific surface area S of the negative electrode active material comprises: testing with a specific surface area tester.

5. A negative electrode active material, characterized in that: The negative electrode active material is obtained by the method for obtaining the negative electrode active material according to any one of claims 1 to 4.

6. A negative electrode sheet, characterized in that: The invention comprises the negative electrode active material as claimed in claim 5 or the negative electrode active material obtained by the method for obtaining the negative electrode active material as claimed in any one of claims 1 to 4.

7. A lithium ion battery, characterized in that: Includes the negative electrode sheet as described in claim 6.

8. Application of the lithium-ion battery according to claim 7 in consumer electronics, electric tools and electric vehicles.

Citation Information

Patent Citations

  • Method for detecting content of surface coating layer of graphite negative electrode material of lithium battery

    CN113405938A

  • Composite material and preparation method thereof, electrochemical device and electronic device

    CN115425215A